Leaders, Perception, and Foreign Policy - Cristiyunisca R. Rongkas; Yohanes Sulaiman (Jurnal Academia Praja, 2019)
How and why images that states and their leaders have toward others change in foreign policy? Literature on psychology, notably on confirmation bias, state that in general, people stick with preconceived ideas that they have in their mind, and they always accept information that support their beliefs, while reject information that contradicts them.[1] And confirmation bias, in turn, affects how a state conducts its foreign policy – that in general, there will always be continuation in a state’s foreign policy, unless there is a systemic shock, caused by dramatic changes in the power distribution.